Once‐a‐Day Controlled‐Release Dosage form of Divalproex Sodium I: Formulation Design and in Vitro/in Vivo Investigations - Qiu, Yihong; Cheskin, Howard S.; Engh, Kevin R.; Poska, Richard P. (Journal of pharmaceutical sciences, 2003)
Divalproex sodium is a narrow therapeutic index drug that is widely used for the treatment of epilepsy, the manic episodes associated with bipolar disorder, and prophylaxis of migraine headaches. The present investigation was undertaken to design an oral dosage form that would provide once‐daily administration with improved therapy and to explore the relationships between in vitro drug release and in vivo absorption. Controlled release hydrophilic matrix formulations of divalproex sodium were designed and evaluated via in vitro and in vivo studies. The release rate of divalproex sodium was modulated by varying different rate‐controlling hydrophilic polymers and measured in vitro using a USP apparatus II dissolution method. Formulations with differing release rates were studied in beagle dogs and in healthy subjects. A selected formulation given once‐daily was further evaluated against the commercial enteric tablet dosed twice‐daily in a multiple dose study, and shown to provide desired nearly constant therapeutic plasma concentrations over the entire 24‐h dosing interval. Preliminary linear relationships between in vitro dissolution and in vivo absorption were observed in both the animal model and in humans. However, the relationships were formulation dependent, indicating a need for further studies. © 2003 Wiley‐Liss, Inc. and the American Pharmaceutical Association J Pharm Sci 92:1166–1173, 2003